Diagnostics and preventive therapy of allergic rhinitis in children: modern algorithm - P.V. Berezhanskiy; A.B. Malakhov; N.A. Geppe; N.G. Kolosova; N.S. Tataurshchikova (LCC «Medicine-Inform», 2023)
P.V. Berezhanskiy1-4, A.B. Malakhov1,3,4, N.A. Geppe1, N.G. Kolosova1, N.S. Tataurshchikova2 1I.M. Sechenov First Moscow State Medical University (Sechenov University), Moscow, Russian Federation 2RUDN University, Moscow, Russian Federation 3Morozov Children's City Clinical Hospital, Moscow, Russian Federation 4Research Clinical Institute of Childhood of the Moscow Region, Moscow, Russian Federation Background: allergic rhinitis (AR) is the leading pathology in pediatric practice. Improvement of the diagnostic accuracy and preventive measures in AR is the priority task. Aim: to evaluate the efficacy of the proposed cascade algorithm of diagnosis and preventive medicated therapy for children at high risk of AR. Patients and Methods: a retrospective epidemiological analysis was conducted in five regions of the Central Federal District for 2017-2021, where the main risk factors of AR were identified. The article proposes a screening cascade and a three-step diagnostic algorithm of AR, as well as high-risk group identification with the indication of preventive medicated therapy. The efficacy of the proposed technique was evaluated in the catamnestic study. Results: during the follow-up, there was a steady increase of AR in all regions - from 1,472 to 2,684%. 28 risk factors were identified, of which 12 were controlled factors. According to the highest risk factor probability, 4 age groups were identified: from birth to 5 years, 6-7 years, 8-12 years and children 13 years and older. In the group receiving preventive therapy, AR was verified in the catamnesis 2 times less common - in 12 instead of 24%. Thus, the patients at high risk of AR require preventive medicated therapy and constant follow-up at certain age periods. Conclusion: this article presents the evaluation of the proposed diagnostic cascade efficacy, the identification of the group at high risk of AR and the justification concerning the use of preventive medicated therapy of AR in this group during acute respiratory infection. Keywords: allergic rhinitis, preventive therapy, polymorphism, heart rate variability, microcirculation. For citation: Berezhanskiy P.V., Malakhov A.B., Geppe N.A., Kolosova N.G., Tataurshchikova N.S. Diagnostics and preventive therapy of allergic rhinitis in children: modern algorithm. Russian Journal of Woman and Child Health. 2023;6(3):276-282 (in Russ.). DOI: 10.32364/2618-8430-2023-6-3-11.